Anda di halaman 1dari 7

Chapter 7

Second Order Partial Differential


Equations

7.1 Introduction
A second order linear PDE in two independent variables (x, y) ∈ Ω can be written as

∂2u ∂2u ∂2u ∂u ∂u


A(x, y) + B(x, y) + C(x, y) + D(x, y) + E(x, y) + F (x, y) u = G(x, y)
∂x2 ∂x∂y ∂y 2 ∂x ∂y
the same in short form can be written as
A(x, y) uxx + B(x, y) uxy + C(x, y) uyy + D(x, y) ux + E(x, y) uy + F (x, y) u = G(x, y) (7.1)

where the subscript(s) represents the partial differentiation with respect to the given
index (indices). Inspired by the classification of the quadratic equations as elliptic,
parabolic and hyperbolic, the second order PDE (7.1) is also classified as elliptic,
parabolic or hyperbolic, at any point (x, y), depending on the value of the discriminant

B2 − 4 A C (7.2)

which is less than, equal to or greater than zero, respectively. Observe that the
coefficients of second order partial derivatives only decide the classification. Three well
known examples for Poisson equation (Elliptic), one-dimensional unsteady diffusion
equation (Parabolic) and one-dimensional wave equation (Hyperbolic) are given by

∂2u ∂2u
+ = f (x, y) (Elliptic) (7.3)
∂x2 ∂x∂y
∂u ∂2u
= K 2 2 (Parabolic) (7.4)
∂t ∂x
∂2u 2 ∂ 2
u
2
= a (Hyperbolic) (7.5)
∂t ∂x2

83
84 Sanyasiraju V S S Yedida sryedida@iitm.ac.in

7.2 Classify the following Second Order PDE


y2 x2
1. y 2uxx − 2xyuxy + x2 uyy = x x
u + y y
u

A = y 2 , B = −2xy, C = x2 ⇒ B 2 − 4AC = 4x2 y 2 − 4x2 y 2 = 0

Therefore, the given equation is Parabolic

2. yuxx + uyy = 0, (Tricomi equation)

A = y, B = 0, C = 1 ⇒ B 2 − 4AC = 0 − 4y = 4

Therefore, the given equation is Hyperbolic for y < 0 and Elliptic for y > 0.

3. uxx − 2uxy + uyy = 0

A = 1, B = −2, C = 1 ⇒ B 2 − 4AC = 4 − 4 = 0

Therefore, the given equation is Parabolic

4. (1 − M 2 )uxx + uyy = 0

A = 1 − M 2 , B = 0, C = 1 ⇒ B 2 − 4AC = 0 − 4(1 − M 2 ) = 0

Therefore, the given equation is Parabolic for M = 1, Elliptic for M < 1 and
Hyperbolic for M > 1.

5. uxx + 2 sin xuxy − cos2 xuyy − cos xuy = 0

A = 1, B = 2 sin x, C = − cosx ⇒ B 2 − 4AC = 4 sin2 x + 4 cos2 x = 4 > 0

Therefore, the given equation is Hyperbolic

6. xuxx + yuyy + xux + yuy = 0

A = x, B = 0, C = y ⇒ B 2 − 4AC = 0 − 4xy

Therefore, the given equation is Parabolic on either of the coordinate axis,


Elliptic in first and third quadrants and finally Hyperbolic in second and fourth
quadrants of the xy-plane.

7. (1 + x2 )uxx + (1 + y 2)uyy + xux + yuy = 0

A = 1 + x2 , B = 0, C = 1 + y 2 ⇒ B 2 − 4AC = 0 − (1 + x2 )(1 + y 2 ) < 0

Therefore, the given equation is Elliptic


Lecture Notes MA2020 Differential Equations 85

7.2.1 Problems to work out: Classify the following PDE


1. (x2 − 1)uxx + 2yuxy − uyy = 0
2. uxx + xuxy + yuyy = 0
3. uxx + (2x + 3)uxy + 6xuyy = 0
4. uxx + 2xuxy + x2 uyy = 0

7.3 Normal or Canonical Form


For hyperbolic equations, there exists two real directions, called characteristic direc-
tions given by

dy B + B 2 − 4AC
= (7.6)
dx √ 2A
dy B − B 2 − 4AC
= (7.7)
dx 2A
Along these directions the partial differential equation takes a simple form called Nor-
mal or Canonical form. Further, the curves (7.6) and (7.7) are called characteristic
curves.

Consider the hyperbolic equation (7.5), for which the characteristic curves can be
obtained using
√ √
dx 4a2 dx 4a2
= and =−
dt 2 dt 2
x − at = C1 and x + at = C2

Therefore, the characteristic curves for (7.5) are given by

ξ = x + at and η = x − at (7.8)

Transforming (7.5) in to ξ and η, using


∂ξ ∂η ∂ξ ∂η
= 1, = 1, = a, = −a
∂x ∂x ∂t ∂t
∂ ∂ ∂ξ ∂ ∂η ∂ ∂
= + = +
∂x ∂ξ ∂x ∂η ∂x ∂ξ ∂η
 
∂ ∂ ∂ξ ∂ ∂η ∂ ∂
= + = a −
∂t ∂ξ ∂t ∂η ∂t ∂ξ ∂η
   
∂2 ∂ ∂ ∂ ∂ ∂ ∂ ∂2 ∂2 ∂2
= + + + = + 2 +
∂x2 ∂ξ ∂ξ ∂η ∂η ∂ξ ∂η ∂ξ 2 ∂ξ∂η ∂η 2
       2 
∂2 ∂ ∂ ∂ ∂ ∂ ∂ 2 ∂ ∂2 ∂2
= a a − −a a − = a −2 +
∂t2 ∂ξ ∂ξ ∂η ∂η ∂ξ ∂η ∂ξ 2 ∂ξ∂η ∂η 2
86 Sanyasiraju V S S Yedida sryedida@iitm.ac.in

gives
   2 
2 ∂2u ∂2u ∂2u 2 ∂ u ∂2u ∂2u
a −2 + = a +2 +
∂ξ 2 ∂ξ∂η ∂η 2 ∂ξ 2 ∂ξ∂η ∂η 2
∂2u ∂2u
4 = 0 ⇒ =0 (7.9)
∂ξ∂η ∂ξ∂η
(7.9) is the normal or characteristic form of (7.5). In general, the normal form of any
hyperbolic equation is
uξη = φ(ξ, η, u, uξ, uη ) or
uξξ − uηη = φ(ξ, η, u, uξ, uη )
Since for the parabolic equations, B 2 − 4AC = 0, therefore, there exists only one real
characteristic direction (curve) given by
dy B
= (7.10)
dx 2A
Along the curves (7.10), parabolic equations, in general, take the form
uηη = φ(ξ, η, u, uξ , uη ) or
uξξ = φ(ξ, η, u, uξ , uη )
If we choose ξ = t and η = x then, (7.4) is already in the form given above for the
parabolic equations.

Finally, since B 2 − 4AC < 0 for elliptic equations, there are no real characteris-
tics for these equations and hence the normal form for these equations will remain
as
uξξ + uηη = φ(ξ, η, u, uξ , uη )

7.3.1 Convert the following PDE in to their normal form


1. uxx + 6uxy + 9uyy = 0
A = 1, B = 6, C = 9 ⇒ B 2 − 4AC = 36 − 36 = 0, Given equation is Parabolic
dy B 6
= = = 3 ⇒ ξ = y − 3x
dx 2A 2
Choose any η which is not parallel to ξ. Let η = x
∂ξ ∂η ∂ξ ∂η
= −3, = 1, = 1, =0
∂x ∂x ∂y ∂y
∂ ∂ ∂ ∂ ∂
= −3 + , =
∂x ∂ξ ∂η ∂y ∂ξ
∂2 ∂2 ∂2 ∂ 2
∂2 ∂2 ∂2 ∂2 ∂2
= 9 − 6 + , = , = −3 2 +
∂x2 ∂ξ 2 ∂ξ∂η ∂η 2 ∂y 2 ∂ξ 2 ∂x∂y ∂ξ ∂ξ∂η
Lecture Notes MA2020 Differential Equations 87

Substituting in the given equation gives


uηη = 0
Which is the required normal form for the given equation. This can be easily
integrated to get
uη = f (ξ) ⇒ u = f (ξ)η + g(ξ) ⇒ u(x, y) = xf (y − 3x) + g(y − 3x)
where f and g are any two arbitrary functions.
2. yuxx + uyy = 0, y = 0
A = y, B = 0, C = 1 ⇒ B 2 − 4AC = −4y = 0
Given equation is Hyperbolic for y < 0 and Elliptic for y > 0

Case i: Hyperbolic (y < 0)

We have
√ √ √ √
dy B+ B 2 − 4AC −4y −y i y i i∗i −1
= = = =√ √ =√ = √ =√
dx 2A 2y y y y y i y −y
Therefore, the transformation is
√ √
ξ = −ydy + dx and η = −ydy − dx
that is
2 2
ξ = − (−y)3/2 + x and η = − (−y)3/2 − x
3 3
 1/3
3
ξx = 1, ηx = −1, ξy = ηy = (ξ + η)
4
  13   13
9 2 √ 3
y=− (ξ + η) 3 , −y = − (ξ + η)
16 4

∂ ∂ ∂
= −
∂x ∂ξ ∂η
  13  
∂ 3 ∂ ∂
= (ξ + η) +
∂y 4 ∂ξ ∂η
∂2 ∂2 ∂2 ∂2
= − 2 +
∂x2 ∂ξ 2 ∂ξ∂η ∂η 2
  23  2 
∂2 3 ∂ ∂2 ∂2
= (ξ + η) +2 +
∂y 2 4 ∂ξ 2 ∂ξ∂η ∂η 2
  13   − 23  
3 1 3 3 ∂ ∂
+ (ξ + η) (ξ + η) ×2 +
4 3 4 4 ∂ξ ∂η
88 Sanyasiraju V S S Yedida sryedida@iitm.ac.in

yuxx + uyy = 0
2
uξ η = − (ξ + η)−1 (uξ + uη )
3
is the required normal form y < 0.

Case ii: Elliptic (y > 0)

We have
√ √ √ √
dy B+ B 2 − 4AC −4y −y i y i
= = = =√ √ =√
dx 2A 2y y y y y

Therefore, the transformation is


√ √
ξ= ydy + idx and η = ydy − idx

that is
2 2
ξ = (y)3/2 + x and η = (y)3/2 − x
3 3

ξ+η 2 ξ−η
α= = y 3/2 , β= =x
2 3 −2i
 1/3  2/3
√ 3 3
αx = 0, βx = −1, αy = y = α , βy = 0, y = α
2 2

∂ ∂
=
∂x ∂β
 1/3
∂ √ ∂ 3 ∂
= y = α
∂y ∂α 2 ∂α
2 2
∂ ∂
2
=
∂x ∂β 2
  23 2   13   − 32 
∂2 3 ∂ 3 1 3 3 ∂
2
= α 2
+ α α
∂y 2 ∂α 2 3 2 2 ∂α

yuxx + uyy = 0
1 1
uα α + uβ β = − uα
3 α
is the required normal form for y > 0.
Lecture Notes MA2020 Differential Equations 89

7.3.2 Problems to workout: Convert the following to their


normal form
1. 2uxx − 2uxy + 5uyy = 0

2. uxx − 2uxy = 0

3. (x2 − 1)uxx + 2yuxy − uyy = 0

4. uxx + xuxy + yuyy = 0

5. uxx + (2x + 3)uxy + 6xuyy = 0

6. uxx + 2xuxy + x2 uyy = 0

7. 4uxx − 4uxy + uyy = 0

8. uxx + xuyy = 0, x = 0
y2 x2
9. y 2uxx − 2xyuxy + x2 uyy = x x
u + y y
u (Optional)

10. (1 + x2 )uxx + (1 + y 2)uyy + xux + yuy = 0 (Optional)

11. uxx − 2 sin x uxy − cos2 x uyy − cos x uy = 0 (Optional)